Trust in primary health care and COVID-19 vaccine uptake among Iranian pediatric: a web-based cross-sectional survey - Ehsan Sarbazi; Nazanin Masoudi; Ahmad Mehri; Robab Mehdizadeh Esfanjani; Hosein Azizi; Maryam Soleimanpour; Mahboub Pouraghaei; Hassan Soleimanpour (BMC, 2024)
Abstract Background Children are the most vulnerable group to diseases. Thus, it's critical to evaluate parents' or guardians' willingness to vaccinate their children. This study aims to investigate the prevalence and predictors of pediatric COVID-19 vaccination in Iran and its relationship with trust in the Primary Health Care (PHC) system. Method A cross-sectional online survey of 549 Iranian parents was conducted between January and March 2023. This study collected data from all provinces of Iran using a questionnaire shared on Google Forms and various social media platforms. After considering various background factors, we used a multivariable logistic regression model. This model explored how trust in the PHC system and parent-related and child-related factors were related to parents' vaccine uptake for their children. Results Of 549 parents aged between 19 and 67 years (median = 38 years), 65.2% (358) were female. The prevalence of vaccine uptake among parents was 46.8%. After adjusting for background features, child's age (adjusted odds ratio [AOR] 0.81, 95% CI 0.71-0.91), vaccine doses (1-dose: AOR 14.72, 95% CI 6.44-33.65, 2-dose: AOR 32.54, 95% CI 15.22-69.57), child's disease (AOR 5.31, 95% CI 2.19-12.85), and trust in PHC (AOR 1.01, 95% CI 1.00-1.02) were associated with parental uptake of the COVID-19 vaccine. Conclusions The findings of this study suggest that the child's age, vaccine doses received, diseases, and trust in PHC are significant predictors of parental uptake of the COVID-19 vaccine for children in Iran. The results can be used in service planning regarding children's COVID-19 vaccination.